1999
DOI: 10.1088/0953-8984/11/16/009
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier localization in investigated by ac conductivity measurements

Abstract: We have investigated the complex ac conductivity of for , temperatures and frequencies . In addition, results from dc measurements are presented. From the frequency dependence of the complex conductivity we find hopping of Anderson-localized charge carriers as the dominant transport process in certain temperature and composition ranges. We deduce that, while Anderson localization is not the driving mechanism for the metal-insulator transition observed in this compound, it is responsible for the high-resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
107
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 54 publications
(69 reference statements)
22
107
0
1
Order By: Relevance
“…The UDR and SU contributions to the intrinsic ac conductivity in the present investigation is consistent with the results for single crystal of LaMnO 3 reported by Seeger et al 15 Since UDR contribution to the ac conductivity is found in a very small region of the frequency, a large error is noticed while analyzing the ac conductivity by the power law for x = 0. The analysis is satisfactory for 0.15 ≤ x ≤ 0.70 by using Eq.…”
Section: B Ac Transportsupporting
confidence: 93%
See 3 more Smart Citations
“…The UDR and SU contributions to the intrinsic ac conductivity in the present investigation is consistent with the results for single crystal of LaMnO 3 reported by Seeger et al 15 Since UDR contribution to the ac conductivity is found in a very small region of the frequency, a large error is noticed while analyzing the ac conductivity by the power law for x = 0. The analysis is satisfactory for 0.15 ≤ x ≤ 0.70 by using Eq.…”
Section: B Ac Transportsupporting
confidence: 93%
“…The deviation from the Arrhenius law at low temperature has also been reported for LaMnO 3 15,17 and other perovskite material, Sr 0.998 Ca 0.002 TiO 3 . 34 The values of E Ma and τ M0 obtained from the Arrhenius fit are E Ma ≈ 53 meV and τ M0 ≈ 3 ×10 −10 s for x = 0 which are in between the reported values 44 meV and 3.3 × 10 −8 s for polycrystalline, 17 and 86 meV and 3 ×10 −13 s for single crystalline 15 Scaling of the electric modulus can give further information about the dependence of the relaxation dynamics on the temperature, structure and also on the concentration of the charge carriers. Top panel of Fig.…”
Section: Electric Modulussupporting
confidence: 67%
See 2 more Smart Citations
“…Solely sample D does not exhibit an MIT, but a weak plateau at 180 K, which is commonly interpreted as a transition between a paramagnetic-insulating to a ferromagnetic-insulating phase and points towards an insufficient doping [40]. Obviously, the low oxygen partial pressure during the deposition of film D is the origin for the deviating R-T characteristics.…”
Section: Resultsmentioning
confidence: 96%